Fostering knowledge sharing through human resource management in R&D teams. (2011) - Chen, Wan-Yu; Hsu, Bi-Fen; Wang, Mei-Ling; Lin, Yen-Yu
Within organisations, employees create, accumulate and share knowledge, often within teams. To increase team effectiveness, today's organisations seek to promote knowledge sharing among their employees. Previous studies of knowledge sharing within organisations have ignored a critical factor: human resource management (HRM). To address this oversight, 52 sets of completed questionnaires from 203 research and development (R&D) employees formed the basis of our empirical analysis, exploring the relationship between HRM and the willingness of team members to share knowledge. We classified team members according to their work values and focused on exploring whether the HRM of teams with different work values would impact knowledge sharing differently. We discuss our findings in terms of their implications for management practices and future research.